Carbapenemase-Producing Klebsiella pneumoniae, a Key Pathogen Set for Global Nosocomial Dominance - Pitout, Johann D D; Nordmann, Patrice; Poirel, Laurent (Antimicrobial agents and chemotherapy, 2015)
The management of infections due to Klebsiella pneumoniae has been complicated by the emergence of antimicrobial resistance, especially to carbapenems. Resistance to carbapenems in K. pneumoniae involves multiple mechanisms, including the production of carbapenemases (e.g., KPC, NDM, VIM, OXA-48-like), as well as alterations in outer membrane permeability mediated by the loss of porins and the upregulation of efflux systems. The latter two mechanisms are often combined with high levels of other types of β-lactamases (e.g., AmpC). K. pneumoniae sequence type 258 (ST258) emerged during the early to mid-2000s as an important human pathogen and has spread extensively throughout the world. ST258 comprises two distinct lineages, namely, clades I and II, and it seems that ST258 is a hybrid clone that was created by a large recombination event between ST11 and ST442. Incompatibility group F plasmids with blaKPC have contributed significantly to the success of ST258. The optimal treatment of infections due to carbapenemase-producing K. pneumoniae remains unknown. Some newer agents show promise for treating infections due to KPC producers; however, effective options for the treatment of NDM producers remain elusive.